Elastic buckling of cylindrical shell under pressure load evaluated on surface - Takeki YAMAMOTO (The Japan Society of Mechanical Engineers, 2019)
This paper presents a numerical procedure using shell element to evaluate the buckling behavior of the cylindrical structure subjected to pressure load. In numerical simulation for pressure vessels using conventional shell elements, the pressure loads imposed to both top and bottom surfaces are expressed as the difference between the internal and external pressures. In this work, the special shell element, in which the surface traction is exactly expressed at the surface, is applied to the buckling analysis. In this approach, the distribution of the transverse normal stress through the thickness can be evaluated. Therefore, the influence of the difference between the internal and the external pressures to the behavior of the buckling of the cylindrical shell structures can be assessed. In the situation that a perturbative load is applied under a certain stress state, bifurcation points are searched by solving a standard eigenvalue problem. Several numerical examples are presented to examine the effectiveness of the proposed approach. The buckling behavior that cannot be considered with the conventional shell elements can be observed by this approach.